The Influence Of Work Life Balance On Employee Performance With Work Ethic As A Moderating Variable - Asmita Wulansari Dg. Liwang; Wulandari; Adrian Polim; Muhamad Risal Tawil; Muhammad Prasha Risfi Silitonga (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study is a quantitative study with an explanatory approach, namely an approach that is backed by previous research to create hypotheses, modify hypotheses, and prove them. The data used in this study are primary data that researchers obtained from employees working at Bugland Furniture spread throughout Indonesia totaling one hundred and seventy-five employees. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the P-Values leading to positive and below the 0.05 significance level, namely 0.002. These results indicate that a good Work Life Balance of an employee can improve physical health, mental health, and financial stability. Ultimately, the three indicators mentioned above can affect Employee Performance. In addition, the Work Ethic variable in this article can also strengthen the influence of the Work Life Balance variable on Employee Performance because of the same thing, namely the P-Values leading to positive and below the 0.05 significance level, namely 0.000. These results indicate that the Work Ethic variable can help the Work Life Balance variable in influencing Employee Performance. On this basis, it can be concluded that the first and second hypotheses in this article can be accepted and proven.